Development of Model Optical Distribution Point Location Detector System with GIS Approach Method- Case Study in PT. Telkom Witel Bandung - Budi Herdiana Budi (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2023)
Principally, the validation of the location of the Optical Distribution Point (ODP) device is carried out to match the field data with the data at the center of the system. The current problem is that there are frequent shifts in ODP location data points in the field with the data system at PT. Telkom Witel Bandung because the existing detection system is still manual. This condition directly disrupts the performance of the communication network system so that service to customers is reduced. Therefore, it is necessary to develop a digital and automatic detection system for detecting ODP locations through the use of the Geographic Information System (GIS) method. This method is able to increase the accuracy and efficiency of the travel time to the ODP location point. This study aims to increase the accuracy of the ODP device at different locations through the development of a location point detection system using the geographic information system method approach. The testing technique carried out in this study used two methods, namely the direct method and the GPS field measure method. The test results on the developed geographic information system have been successfully integrated with Google maps and the GPS sensor has been successfully sent to the application. The results of the previous system obtained a location accuracy rate with an error percentage value of 3.6%. While the results of this development system obtained an error percentage value of 1%. Based on the results of the final test, it shows that the system developed in this study produces a better accuracy value than the previous system. In the future, this developed system can be implemented to accurately detect ODP locations for larger numbers and larger areas.